IMPORTED ELEGANCE: INVESTIGATING THE INTERPLAY OF COUNTRY OF ORIGIN, PRODUCT KNOWLEDGE, AND BRAND IMAGE INFLUENCES ON CONSUMER PURCHASE DECISION IN THE AUTOMOBILE BRANDS - Johanes Ronaldy Polla; Elia Oey (Green Publisher, 2024)
This study explores the complex relationships that influence consumers' decisions to buy foreign car brands. In order to understand how these three crucial elements together affect customers' choices and preferences, the study focuses on three key variables: brand image, product knowledge, and country of origin (COO). Using a thorough approach that includes surveys and case studies, this study attempts to offer a nuanced understanding of how the origin, consumer product knowledge, and brand image of imported vehicles affect the perceived elegance associated with consumers. The study postulates that customers' decision-making process while choosing an imported car is greatly influenced by the interaction of these elements. This research aims to provide significant insights to the automobile industry as well as academics by examining the relationships and conflicts that exist between COO, product knowledge, and brand image. Marketers, politicians, and industry stakeholders might find the findings useful in fine-tuning tactics to improve the attractiveness and market placement of imported automobile brands.